2015
DOI: 10.1055/s-0034-1543953
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Prolonged Postpartum Length of Stay Following Cesarean Delivery

Abstract: Objective This study aims to identify risk factors for prolonged postpartum length of stays (LOS) after cesarean delivery (CD). Study Design Patients undergoing CD were sourced from a multicenter registry of 19 academic centers between 1999 and 2002 (n = 57,067). Prolonged postpartum LOS was defined as a hospitalization duration ≥ 90th centile. Maternal, antepartum, perioperative, and neonatal variables were compared between women with and without prolonged postpartum LOS. Results The 90th centile for post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 26 publications
0
25
0
2
Order By: Relevance
“…The growing cost of hospital stays is one of the factors for early discharge [36]. In addition to this, Blumenfeld found that younger and older women (less than 20 years or more than 34 years of age) who have insurance are more likely to stay for long after birth [2].…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The growing cost of hospital stays is one of the factors for early discharge [36]. In addition to this, Blumenfeld found that younger and older women (less than 20 years or more than 34 years of age) who have insurance are more likely to stay for long after birth [2].…”
Section: Studymentioning
confidence: 99%
“…Global efforts to prevent maternal and perinatal mortality aim to ensure all women have access to skilled attendants for childbirth, which in practice is synonymous with advocating for both facility delivery and home birth. In the twentieth century, a higher proportion of births occurred in a facility/hospital than at home [1][2][3]. The maternal mortality ratio (MMR) in India had declined by 124 points from 254 maternal deaths per 100,000 live births in 2006 to 130 in 2016 [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation in the choice of covariates and not being able to include health status information likely lead to the underestimation of the mean LOS. Individual patient comorbidities are unlikely to substantially change prediction of components (shorter LOS and longer LOS distributions) [40,41]. As with modeling in general the effect of a parameter changes depending on the other covariates in the model.…”
Section: Plos Onementioning
confidence: 99%
“…Bacterial infections during labour and the puerperium are among the leading causes of maternal morbidity and mortality worldwide [1,2]. Postpartum endometritis is the most common infectious complications following childbirth and occurs in women from 1% to 30% [3][4][5][6][7][8][9]. This infection is more common after cesarean section than with vaginal delivery [10].…”
Section: Introductionmentioning
confidence: 99%